The Importance of Regional Magazines for Affirmation of Homeland Traditions and Cultural Heritage - Deletić, Zdravko (Collection of Papers of the Faculty of Philosophy in Priština, 2020)
Local magazines are a suitable medium for presenting and affirming native history, traditions, and cultural heritage. They provide an opportunity for affirmation of values that are significant at the local level but not researched and visible at the national level—they have no national or international significance. Local media allow the presentation of creativity and affirmation of under-proven creators, amateurs, as well as initial steps for young creators in the field of literature. Problems in the field of funding, author competence, editing, peer review, and scientific reach of published works are a reality. However, these are problems that need to be addressed, not to challenge the importance and necessity of having local magazines. The paper was written on the basis of personal author and editorial experience, analysis of the content of local journals in the north of Montenegro, study of the methodology of scientific work, and theoretical reflection on the given topic.  The paper was written on the basis of personal author and editorial experience, analysis of the content of local journals in the north of Montenegro, study of the methodology of scientific work and theoretical reflection on a given topic.
Keywords: homeland; history; tradition; cultural heritage